The relationship between health literacy and self-management behaviour in type 2 diabetes mellitus adults - Wong, Xiao Vee (2022)
The prevalence of Type 2 Diabetes Mellitus (T2DM) is increasing and the prevalence of health literacy among Malaysian is low. T2DM is a condition that requires the diagnosed adults to practise self-management behaviour as appropriate management of their condition which will lead to approximate normal life. However, the variables affecting the self-management behaviour of T2DM adults are not well understood. Hence, this study aims to determine the relationship between health literacy and self-management behaviour of T2DM adults. A cross-sectional study was done on 112 T2DM adults across Malaysia. The data were collected using the questionnaire that consists of three sections, which were sociodemographic, Health Literacy Survey Malaysian Questionnaire18 (HLS-M-Q18) and Diabetes Self-Management Questionnaire (DSMQ). Data were analysed using descriptive statistics, One way analysis of variance (ANOVA) and Independent T-Test. Results indicated that 75.9% of the T2DM adults have limited health literacy. The self-management behaviour mean score of 4.94 ± 1.54 (poor) was found. Health care use was the most practised (Mean = 7.78 ± 1.94) among the four subscales while physical activity is the least practised (Mean = 2.50 ± 3.12) by T2DM adults. A significant relationship was found between health literacy and self-management (p < 0.001) of the T2DM adults whereby the lower the health literacy, the poorer the self-management behaviour of T2DM adults. Sociodemographic variables of age (p = 0.002), education level (p < 0.001) and duration diagnosed with T2DM (p < 0.001) showed a significant relationship with self-management behaviour of T2DM adults. Therefore, it was concluded that a significant relationship was found between health literacy and self-management behaviour. Appropriate strategies should be planned to increase the health literacy of T2DM adults as it will lead to better self-management behaviour. Future studies should explore on the factors that affect the self-management behaviour of T2DM adults.